The confiscation of Jewish property in the Protectorate of Bohemia and Moravia - Jaromír Tauchen (Journal on European History of Law, 2011)
This contribution deals with the anti-Jewish property regulations, which were issued during the period of the Protectorate of Bohemia and Moravia (1939 - 1945). Attention is paid to both, the regulations of the Protectorate Ministries and to the regulations of the Reich Protector of Bohemia and Moravia, the most important being the Decree about Jewish property from June 1939.